2010
DOI: 10.1021/ef1004557
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Acids and Neutral Nitrogen Compounds in a Chinese Crude Oil and Its Fractions: Characterized by Negative-Ion Electrospray Ionization Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: A Chinese crude oil was distilled into multiple narrow boiling fractions. The crude oil, 39 narrow distillate fractions (up to 560 °C), and atmospheric and vacuum residues were analyzed using negative electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR MS). The heteroatoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
161
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(188 citation statements)
references
References 40 publications
14
161
1
7
Order By: Relevance
“…O2 is the most abundant heteroatom class in our studies. This is different from the results reported by Shi et al (2010b) on a non-biodegraded oil from Liaohe Basin in which the N1 class was most abundant. This difference can be attributed to the selective removal of N1 class and/or the generation of O2 class during biodegradation.…”
Section: Compound Class Distributioncontrasting
confidence: 99%
See 3 more Smart Citations
“…O2 is the most abundant heteroatom class in our studies. This is different from the results reported by Shi et al (2010b) on a non-biodegraded oil from Liaohe Basin in which the N1 class was most abundant. This difference can be attributed to the selective removal of N1 class and/or the generation of O2 class during biodegradation.…”
Section: Compound Class Distributioncontrasting
confidence: 99%
“…The O2 species with DBE values of 2-7 are naphthenic acids of 1-6 naphthenic rings, which have been confirmed by GC-MS and MS using various ionization techniques (Shi et al, 2010b). The species with a DBE of 5 are likely 4-ring steroidal acids (Seifert et al, 1972;Rodrigues et al, 2000;Peters et al, 2005) and/or secohopanoic acids (Nascimento et al, 1999;Shi et al, 2010b).…”
Section: O2 Classmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies showed that through chemical methylation treatment, thioether, and thiophenic etc. OSCs in crude oil can be ionized for selective oxidation in the Electrospray Ionization (ESI) mode (Müller et al, 2005;Shi et al, 2010aShi et al, , 2010bPan et al, 2010;Liu et al, , 2010bLiu et al, , 2011, or in the Atmospheric Pressure Photo-Ionization (APPI) mode (Purcell et al, 2007;Liu et al, , 2010b in order to conduct FT-ICR MS analysis to characterize their distributions.…”
mentioning
confidence: 99%